Christianization in Early Medieval Transylvania
1 online resource.
Keywords: Little is known about the Christianization of east-central and eastern Europe, due to the fragmentary nature of the historical record. Yet occasionally, unexpected archaeological discoveries can offer fresh angles and new insights. This volume presents such an example: the discovery of a Byzantine-like church in Alba Iulia, Transylvania, dating from the 10th century - a unique find in terms of both age and function. Next to its ruins, another church was built at the end of the 11th century, following a Roman Catholic architectural model, soon to become the seat of the Latin bishopric of Transylvania. Who built the older, Byzantine-style church, and what was the political, religious and cultural context of the church? How does this new discovery affect our perception of the ecclesiastical history of Transylvania? A new reading of the archaeological and historical record prompted by these questions is presented here, thereby opening up new challenges for further research. Contributors are: Daniela Marcu Istrate, Florin Curta, Horia I. Ciugudean, Aurel Dragotă, Monica-Elena Popescu, Călin Cosma, Tudor Sălăgean, Jan Nicolae, Dan Ioan Mureșan, Alexandru Madgearu, Gábor Thoroczkay, Éva Tóth-Révész, Boris Stojkovski, Șerban Turcuș, Adinel C. Dincă, Mihai Kovács, Nicolae Călin Chifăr, Marius Mihail Păsculescu, and Ana Dumitran.